A high-quality, haplotype-phased genome reconstruction reveals unexpected haplotype diversity in a pearl oyster. (10th November 2022) - Takeuchi, Takeshi; Suzuki, Yoshihiko; Watabe, Shugo; Nagai, Kiyohito; Masaoka, Tetsuji; Fujie, Manabu; Kawamitsu, Mayumi; Satoh, Noriyuki; Myers, Eugene W
Abstract: Homologous chromosomes in the diploid genome are thought to contain equivalent genetic information, but this common concept has not been fully verified in animal genomes with high heterozygosity. Here we report a near-complete, haplotype-phased, genome assembly of the pearl oyster, Pinctada fucata, using hi-fidelity (HiFi) long reads and chromosome conformation capture data. This assembly includes 14 pairs of long scaffolds (>38 Mb) corresponding to chromosomes (2 n = 28). The accuracy of the assembly, as measured by an analysis of k -mers, is estimated to be 99.99997%. Moreover, the haplotypes contain 95.2% and 95.9%, respectively, complete and single-copy BUSCO genes, demonstrating the high quality of the assembly. Transposons comprise 53.3% of the assembly and are a major contributor to structural variations. Despite overall collinearity between haplotypes, one of the chromosomal scaffolds contains megabase-scale non-syntenic regions, which necessarily have never been detected and resolved in conventional haplotype-merged assemblies. These regions encode expanded gene families of NACHT, DZIP3/hRUL138-like HEPN, and immunoglobulin domains, multiplying the immunity gene repertoire, which we hypothesize is important for the innate immune capability of pearl oysters. The pearl oyster genome provides insight into remarkable haplotype diversity in animals.